Análisis e influencia de la producción en los resultados de Gestión Energética que aplica la empresa Shanantina S.A.C periodo 2013 – 2014. - Barón Ramírez, Milagros (2015)
With this research, the relationship between electricity use and production company SAC was determined Shanantina period 2013-2014. The study aims to determine the influence of production in the results of energy management company that develops Shanantina SAC 2013-2014. The population constitutes the registration of electricity consumption in the processing plant sacha inchi . The research results show that the production company Shanantina SAC is the most influential factor in the results of energy management, affirmation backed by a determination coefficient of 83.06% , also the results show that energy is not associated with production is determined by the rate of 231.18, indicating potential savings for the company.